Implementation of MATLAB Based Flux Linkage Characteristics Model of 8/6 SRM - Yogesh Pahariya; Rakesh Saxena (Institute of Advanced Engineering and Science, 2013)
This paper is describes the method of measuring the flux linkage versus current and rotor position of SRM for submersible pump application. The knowledge of flux linkage characteristics of motor is utilized for determination of performance of motor, design of converter and rotor position. Proposed experimental setup is finding the flux linkage characteristics of motor and their modeling in MATLAB is also designed using Fourier cosine coefficients. Developed model is compared with experimental results.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.1842